In Hipertansion Patients Affects of Quinapril and Nebivolol on QT Dispersion - Korkmaz, Hasan; Önalan, Orhan; Akbulut, Mehmet; Karaca, Ilgın; Özbay, Yılmaz; Erdem, Kenan (Fırat University, 2007)
Objectives: QT dispersion (QTD) is thought to reflect spatial heterogeneity of ventricular refractoriness. We aimed to investigate and compare the effect of nebivolol and Quinapril on the QTD in patients with hypertension. Material and Methods: Patients with established or newly diagnosed hypertension were included. The QT interval was measured in all leads from a standard 12-lead ECG and QTD was defined as the difference between the maximum and minimum QT interval. The QTD values were corrected for heart rate using Bazett's formula (QTDC). Results: Groups (Quinapril, n= 27, Nebivolol, n=27) were similar with respect to demografic, echocardiographic, biochemichal and clinical variables. After four weeks of tretament a significant reduction was observed in systolic (p

Giriş: QT interval dispersiyonunun (QTD) ventrikül repolarizasyon inhomojenitesinin bir göstergesi olduğu düşünülmektedir. Bu çalışmada hipertansif hastalarda kısa süreli nebivolol ve kinapril tedavisinin QTD üzerine olan etkilerinin araştırılması amaçlandı. Gereç ve Yöntem: İlaç kullanmayan veya yeni tanı almış hipertansif hastalara sırasıyla kinapril veya nebivolol tedavisi başlandı. QT intervali yüzeyel EKG’de Q dalgasının başından T dalgasının sonuna kadar olan mesafe olarak ölçüldü ve değerler (QTC) Bazett formülü ile kalp hızına göre düzeltildi. Maximum ve minimum QT intervalleri arasındaki fark QTD olarak tanımlandı. Bulgular: Gruplar (Kinapril, n= 27, Nebivolol, n=27) demografik, ekokardiyografik, biyokimyasal ve klinik değişkenler bakımından benzerdi. Dört haftalık bir tedavi sonunda SKB (her iki grupta da p
Hipertansif Hastalarda Kinapril ve Nebivolol’ün QT Dispersiyonu Üzerine Etkileri